Efektivitas Layanan Bimbingan Kelompok untuk Mereduksi Body Image Negatif Siswa Sekolah Menengah Kejuruan Negeri 1 Sungai Penuh - Harmalis, Harmalis; Juliawati, Dosi; Marzulina, Palyasil; Prasetia, Agung Tri; Guspriadi, Yan (Jurnal Aplikasi IPTEK Indonesia, 2024)
This research is motivated by the existence of students who feel dissatisfied with the shape and size of their body, dissatisfied with their appearance, embarrassed if acne appears, feel they have a height that is not ideal, do not have a proportional body, and are not confident with a dark skin color. So efforts are needed to reduce negative body image to positive in students through group guidance services. The objectives of this study are 1) To reveal the form of the negative body image of students before being given group guidance services, 2) To reveal the negative body image of students after being given group guidance services, and 3) To reveal whether group guidance services are very effective for reducing negative body image before and after services are provided to students. This type of research is an experiment with a one-group pretest-posttest design with a population of 243 students of SMK Negeri 1 Sungai Penuh. The implementation of group guidance services was carried out for 6 meetings. The instrument used is the body image scale using 30 items. The data analysis used is the norm of categorization of respondents' achievements and the Wilcoxon test. Based on data analysis, it is found that there is a significant difference in body image conditions before and after being given group guidance services to X and XI grade students of SMK Negeri 1 Sungai Penuh